2015
DOI: 10.1128/aac.00504-15
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Double-Blind, Randomized, Phase 2 Study Evaluating the Novel Antibiotic Cadazolid in Patients with Clostridium difficile Infection

Abstract: C lostridium difficile infection (CDI), the main cause of nosocomial infectious diarrhea, results from the growth of toxinproducing C. difficile in the colon following disruption of the normal enteric microbiota, usually as a consequence of antibiotic therapy (1). The frequency and severity of CDI have risen over the past decade, with associated increases in morbidity and mortality, especially among the elderly (2, 3). The increase in CDI has been attributed, at least in part, to the epidemic C. difficile BI/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 20 publications
2
43
0
1
Order By: Relevance
“…This surveillance forms a baseline for future comparisons as fidaxomicin use becomes more common and other new agents are introduced for the treatment of C. difficile-associated disease (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…This surveillance forms a baseline for future comparisons as fidaxomicin use becomes more common and other new agents are introduced for the treatment of C. difficile-associated disease (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects following a single 3000 mg oral cadazolid dose, the majority of the oral dose (94%) was recovered as unchanged drug in the faeces [11]. Cadazolid doses of 250, 500 and 1000 mg twice daily for 10 days were effective in the treatment of patients with CDI [12]. Clinical cure rates were similar to vancomycin while having lower recurrence rates, resulting in higher sustained cure rates [12].…”
Section: Introductionmentioning
confidence: 93%
“…Cadazolid has previously been shown to be well tolerated in healthy subjects and subjects with CDI [11,12]. In both populations, very low cadazolid systemic exposures were observed following both single and multiple oral doses [11].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…CDZ exhibited potent in vitro activity not only against C. difficile clinical isolates but also against VRE (MIC 90 , 2 g/ml) (12, 13), while having a limited impact on bacteria of the normal gut microflora in the in vitro human gut model (14). Recently, a phase 2 trial in CDAD showed clinical cure rates with CDZ treatment similar to those with VAN treatment, while having lower recurrence rates, resulting in higher sustained cure rates (15).…”
mentioning
confidence: 99%